The role of aquaculture in the international trade of giant clams (Tridacninae) for the aquarium industry (2001–2019) - Vogel, Maite L.; Hoeksema, Bert W. (Aquaculture, 2024)
An overview over the international trade in live giant clams (Bivalvia: Tridacninae) from 2001 to 2019 was made based on worldwide import data from the CITES Trade Database. A distinction was made between trade records of wild-caught clams and maricultured ones. A general decline in the trade of wild giant clams was observed. Since these bivalves naturally live attached to rocky substrate in coral reefs and their forceful removal is harmful to surrounding corals, this trend helped to prevent damage to their natural environment. Possible reasons behind this decline are lower population numbers, trade restrictions, and a decrease in demand. Trade in wild-caught Tridacna crocea decreased, whereas that of T. maxima increased, taking over the former's position as most popular species. From 2015 onwards, over 50% of the source was made up by aquaculture, up to 2019. Aquaculture of live giant clams can be profitable, but there are still obstacles to overcome in order to ensure stable production numbers and long-term profit. With more research and support from governments, aquaculture can help to take pressure off wild populations of giant clams that are already suffering from exploitation for the sea-food market and souvenir industry, and also from habitat degradation due to climate change and other anthropogenic disturbances. •The international trade in giant clams for the aquarium industry declined during 2001–2019.•This decline was caused by less trade in wild-caught animals.•International trade in cultivated clams did not change significantly but became dominant.•Harvesting of wild giant clams can be harmful to their natural environment, mostly coral reefs.•Aquaculture of giant clams can help to take pressure off wild populations.